2017
DOI: 10.18632/oncotarget.19313
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram to predict HER2 status in breast cancer patients with HER2-borderline disease as determined via immunohistochemistry

Abstract: This study aimed to develop a nomogram to predict fluorescence in situ hybridization (FISH) assay results for HER2-borderline breast cancer as determined via immunohistochemistry (IHC) among patients in China. We reviewed a database of breast cancer patients diagnosed between January 2007 and April 2013 at our institutions. We used logistic regression to develop a nomogram and we used receiver operating characteristic curve analysis and calibration plots to validate our nomogram. In total, 1138, 301 and 344 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 43 publications
(32 reference statements)
2
11
2
Order By: Relevance
“…The prevalence of HER2 positivity in borderline HER2 in our study was similar to a large cohort of patients in India, which was estimated as 14.6% [5]. However, in numerous studies, the rate of HER2 ampli cation by FISH in IHC borderline tumors was higher than the present study, from 27.5% to 70 % [10][11][12][13][14]. The reason for such a high reported rate was explained in some of the publications.…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of HER2 positivity in borderline HER2 in our study was similar to a large cohort of patients in India, which was estimated as 14.6% [5]. However, in numerous studies, the rate of HER2 ampli cation by FISH in IHC borderline tumors was higher than the present study, from 27.5% to 70 % [10][11][12][13][14]. The reason for such a high reported rate was explained in some of the publications.…”
Section: Discussionsupporting
confidence: 83%
“…A radiomics nomogram was established incorporating ER status and com-rad-score. The nomogram yielded an AUC of 0.848 in the validation cohort, which was higher than that of previous nomograms for HER-2 2+ status determination that only used clinicopathologic characteristics of BC (AUC: 0.749) [6]. The nomogram also achieved a higher AUC than the com-rad-score.…”
Section: Discussionmentioning
confidence: 68%
“…According to IHC results, a HER-2 staining intensity score of 3+ is considered positive, whereas a score of 0 or 1+ is considered negative. However, IHC cannot identify HER-2 2+ status, which accounted for approximately 17% of HER-2 patients [6], and a fluorescence in-situ hybridization (FISH) assay is required. Identification of gene amplification via FISH classifies tumors into positive or negative according to the HER-2 2+ status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study from Morocco which included 1508 patients found that overexpression of HER2 was associated with high tumor grade, vascular space invasion and ER negativity significantly [21]. Another study from a single center in China suggested that ER status, PR status and tumor grade were significantly associated with HER2 status [22]. Different studies from different institution indicated the same finding that HER2 overexpression is correlated with HR negativity, while the relationship between HER2 expression and other clinicopathologic parameters varies, such as tumor dimension, nodal involvement and tumor grading.…”
Section: Discussionmentioning
confidence: 99%